2016
DOI: 10.2147/opth.s106455
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled study of oral antioxidant supplement therapy in patients with dry eye syndrome

Abstract: PurposeTo evaluate the efficacy of oral antioxidant supplementation in the treatment of patients with dry eye syndrome (DES).MethodsA prospective, randomized, double-blinded study compared the effects of an antioxidant supplement (containing anthocyanosides, astaxanthin, vitamins A, C, and E, and several herbal extracts, including Cassiae semen and Ophiopogonis japonicus) with placebo on patients with DES. We assessed dry eye symptoms, visual acuity, Schirmer’s test, tear film breakup time, cornea and conjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 42 publications
(37 reference statements)
0
10
0
1
Order By: Relevance
“…A randomized controlled trial investigated the efficacy of an antioxidant supplementation consisting of anthocyanosides, astaxanthin, vitamins A, C, E and several herbal extracts, such Cassiae semen and Ophiopogonis japonicas in the treatment of patients with DED. After therapy, objective parameters including reactive oxygen species tear levels, Schirmer test, tear break-up time and corneal fluorescein staining significantly improved, confirming the efficacy of such preparation in enhancing lacrimal gland function, tear film stability and decreasing epithelial damage [87].…”
Section: Vitamin Cmentioning
confidence: 64%
See 1 more Smart Citation
“…A randomized controlled trial investigated the efficacy of an antioxidant supplementation consisting of anthocyanosides, astaxanthin, vitamins A, C, E and several herbal extracts, such Cassiae semen and Ophiopogonis japonicas in the treatment of patients with DED. After therapy, objective parameters including reactive oxygen species tear levels, Schirmer test, tear break-up time and corneal fluorescein staining significantly improved, confirming the efficacy of such preparation in enhancing lacrimal gland function, tear film stability and decreasing epithelial damage [87].…”
Section: Vitamin Cmentioning
confidence: 64%
“…By promoting the production of surfactants, it incorporates the lipid component of tear film and tear substitutes, thus stabilizing the ocular surface system. Finally, it modulates systemic calcium absorption, which has a crucial role in maintaining a fluid secretion in both salivary and lacrimal glands [87]. Serum levels of vitamin D have shown significant correlations with tear production, stability and DE symptoms [89,90].…”
Section: Vitamin Dmentioning
confidence: 99%
“…[5]. Наконец, он модулирует системную абсорбцию кальция, которая играет решающую роль в поддержа нии секреции жидкости как в слюнных, так и в слезных железах [6]. Сывороточные уровни витамина D показа ли значимые корреляции с продукцией слезы, стабиль ностью слезной пленки и выраженностью симптомов синдрома сухого глаза (ССГ) [7].…”
Section: витамин еunclassified
“…The supplementation period lasted 8 weeks and patients were followed up every 4 weeks for 16 weeks. Results showed that oral micronutrients supplementation significantly improved tear production and stability while decreased corneal fluorescein staining and tear ROS levels, thus leading to a significant amelioration in both signs and symptoms [65]. The rationale of the use of astaxanthin derives from its capacity to directly address the vicious cycle of the disease, and in particular the underlying inflammation and oxidative stress.…”
Section: Ocular Surfacementioning
confidence: 99%